Outcome of Three Dimensional Printed Functional Prostheses for Children with Upper Limb Deficiency in Nepal - Shrestha, S; Gautam, S (Kathmandu University Medical Journal, 2023)
Background Children with congenital and traumatic upper limb amputation are undervalued in a low and middle-income country (LMIC) like Nepal. The use of a prosthetic hand can give them a feeling of self-reliance to perform their daily activities. However, prosthesis require periodic maintenance and replacement which could be a financial burden to some families. The e-Nable community has designed and developed three dimension printed prosthetic hands for children under 19 years old, and distributed them free of cost.Objective To explore the functionality of the three dimension printed prosthetic hands using semi-structured questionnaires and assess a series of daily tasks after three months prosthetic use.Method This descriptive cross-sectional study was conducted from July 2019 to June 2020, after receiving an ethical clearance from the Nepal Health Research Council (Registration number: 582/2019). Seventy six children (5-18 years old) who met the inclusion criteria were enrolled in this study. Data were collected using semi-structured questionnaires, and observational methods to identify the benefits and drawbacks of the three dimensional prosthetic hands. Mean, standard deviation, and percentage were used to interpret the data.Result All participants could only lift light objects such as tray, tennis ball or a bottle of water. They had difficulty with those task that required complex movement and with lifting heavy objects. Moreover, only 47(61.8%) participants were completely satisfied with the prosthetic hand and the major reasons for dissatisfaction were tear of the rubber band or cord, and broken parts.Conclusion Participant were able to complete certain tasks using the e-Nable community three dimensional printed prosthetic hands.